Phycocyanobilin in solution – a solvent triggered molecular switch - Watermann, Tobias; Elgabarty, Hossam; Sebastiani, Daniel (Phys. Chem. Chem. Phys.)
The chromophore phycocyanobilin changes its spectroscopic behaviour upon solvent change. Our calculations trace this effect back to conformational switching, induced by changes in the hydrogen bonding pattern.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Intermediale Lektüre(n). Ein Konzept für Zu- und Übergänge in intermedialen Lehr- und Lernarrangements - Kruse, Iris (Kinder- und Jugendliteratur in Medienkontexten. Adaption – Hybridisierung – Intermedialität - Konvergenz)

Märchenbilder im Medienverbund. Zugänge zu komplexen Märchenbilderbüchern durch intermediale Lernumgebungen - Kruse, Iris (Bilderbuch und literar-ästhetische Bildung - aktuelle Forschungsperspektiven)

...aber das Buch mag ich jetzt auch! Der kleine Ritter Trenk im medienvergleichenden Zugriff von Vor- und Grundschulkindern - Kruse, Iris (Kirsten Boie. Bielefelder Poet in Residence 2013)

Brauchen wir eine Medienverbunddidaktik? Zur Funktion kinderliterarischer Medienverbünde im Literaturunterricht der Primar- und frühen Sekundarstufe - Kruse, Iris (Leseräume – Zeitschrift für Literalität in Schule und Forschung)

Die (Un-)Wirksamkeit der Warnung. Zur Rezeption ökologischer Dystopien - Kruse, Iris (JuLit)

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

Bewegungsbaustellen, Bewegungsräume und Bewegungslandschaften - Albers, Timm (Bewegungserziehung in der frühen Kindheit - wissenschaftliche Grundlagen)

Bewegung macht Sinn: Selbstwirksamkeitserleben im Sportunterricht der Primarstufe - Albers, Timm (Fördermagazin Grundschule)

Kooperation von allgemein und sonderpädagogischen Lehrkräften im Unterricht - Albers, Timm
Keywords: s2n; Scan2Net